PINJAMAN DANA BERGULIR DALAM PERSPEKTIF EKONOMI ISLAM - jenita jenita; rustam rustam; deni marfikuillah (Universitas Lancang Kuning, 2017)
Abstract: This research method is a library reseach with the normative approach, namely byreviewing the concept, economic theories related to the issues discussed.The object ofresearch revolving fund with research subjects is a revolving fund in the perspective ofIslamic economics. data sources using primary data and secondary data. The primary data isobtained directly on data collected from actual situation when events are linked to theimplementation of a revolving fund that is implemented by the government. Secondary data,ie data gathered from the hand of both or from other sources that are willing to before thestudy is done. Data obtained in this research is to conduct library research and the datarelatingData collection techniques or literature is a literature review. Technique analysis datawere analyzed diskriftif normative form of presentation in narrative form. Where the results ofthe analysis will be presented descriptively, with the hope to describe clearly the revolvingfund in the perspective of Islamic economics. Based on the analysis of the implementation ofa revolving loan fund which is implemented by the government in the economic perspectivesof Islam that the notion of a revolving loan fund which is implemented by the currentgovernment tends to apply the system of interest is identified as a motive to increase theamount of funds or gain. In a survey of Islamic economics, such as revolving loan funds can’tbe applied. It because there are some errors occurring in the implementation of lending.Among these errors are lending fund still use the laptop, by the additional costs of the loanprincipal. In the rules of jurisprudence states